Potensi Pengembangan Plastik Biodegradable Berbasis Pati Sagu Dan Ubikayu Di Indonesia - Elmi Kamsiati; Heny Herawati; Endang Yuli Purwani (Badan Penelitian dan Pengembangan Pertanian, 2017)
Plastic is a packaging materials that are widely used but has an adverse impact on the environment because it is difficult to degrade in nature. Production technology of biodegradable plastics from natural resources that have characteristic environmentally friendly has developed. Starch-based biodegradable plastic is a widely developed type because the production process is simple and the raw materials more readily available. The starch of cassava and sago has potential as a raw material of biodegradable plastic because of the availability and its characteristic. Also, to make starch as the main ingredient, plasticizers and structural strengthening materials are required to produce biodegradable plastic with excellent characteristics. The production stages of biodegradable plastics include mixing, heating, and casting. The starch-based biodegradable plastic that can apply to an environmentally friendly packaging material has an excellent opportunity developed in Indonesia.Keywords: Starch, sago, cassava, biodegradable plastics, production technology AbstrakPlastik merupakan bahan pengemas yang banyak digunakan namun berdampak buruk bagi lingkungan karena sulit terdegradasi di alam. Teknologi produksi plastik biodegradable atau bioplastik yang dibuat dari bahan alami dan ramah lingkungan sudah mulai dikembangkan. Plastik biodegradable berbahan dasar pati relatif lebih mudah diproduksi dan bahan baku mudah diperoleh. Pati ubi kayu dan sagu memiliki potensi sebagai bahan baku plastik biodegradable ditinjau dari ketersediaan dan karakteristiknya. Selain pati sebagai bahan utama, diperlukan pula plastisizer atau bahan pemlastis dan bahan penguat struktur untuk menghasilkan plastik biodegradable dengan karakteristik yang baik. Tahapan produksinya meliputi pencampuran, pemanasan, dan pencetakan. Plastik biodegradable berbahan dasar pati dapat digunakan sebagai bahan pengemas yang ramah lingkungan dan berpeluang besar dikembangkan.Kata kunci: Pati, sagu, ubi kayu, bioplastik, teknologi produksi